Histological evaluation of bone metabolism discrepancies resulting from Neuroligin 3 and 4 Knockout in Autistic Mouse Model - Glaser, Julia Janine; Justus Liebig University Giessen (My University, 2025)
A foundational understanding of bone metabolism at the cellular level in pre-clinical autistic models could potentially aid in preserving bone quality, given that higher fracture rates have been observed in patients with ASD. Autism Spectrum Disorder (ASD) is not solely a neurodevelopmental condition; it also exerts significant effects on bone structure and metabolism. Several publications have documented an elevated risk of fractures in both pediatric and adult populations with ASD, alongside findings of reduced bone thickness, which correlates with an increased fracture risk (34). The risk of bone fractures in individuals with ASD may be approximately 30% to 50% higher compared to those without ASD (37). These percentages are estimates and may vary based on factors such as age, severity of ASD symptoms, comorbidities, and other individual characteristics. Further detailed analyses are required to investigate the influence of genetic alterations on bone metabolism. Therefore, we conducted radiological, enzyme- and immunohistochemical evaluations alongside investigating macrophage activity in bone. Radiological assessments did not confirm the differences reported in the literature between wild-type and knockout groups. Histomorphometry revealed a narrowed growth plate in the NL4 knockout group. Conversely, the NL3 knockout group showed significantly increased osteoclast activity, indicating a potential imbalance in bone turnover. The percentage of osteoblasts in the NL4 knockout group was four times higher compared to the other groups. Immunohistochemically, an increased presence of immune cells was observed in the knockout groups. In the NL4 knockout group, there was an increased presence of macrophages in stage M1, suggesting a prevailing pro- inflammatory metabolic state. Initial research suggests that macrophages have a crucial role in the process of fracture healing (4,5,20). The regulatory patterns of macrophages represent a potential target for improving bone quality by modulating their involvement in the remodeling process of immune cells. Also noteworthy in histological analysis was the increased number of osteoblasts and osteoclasts in the NL3 knockout group compared to the other groups, which may have metabolic and cellular relevance. As a prospect for future research endeavors, there is a need to focus on the qualitative properties of bone, whereas this study centered on quantitative examination of bone structure. Further intracellular investigations are now required to contextualize the observed quantitative changes in relation to a potentially poorer quality of bone structure.
Keywords: Autismus; Knochenstoffwechsel; Knockout Mäuse; Histologie; Neuroligin; ddc:610